2008
DOI: 10.2353/ajpath.2008.070604
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 12 Accelerates the Initiation of Atherosclerosis and Stimulates the Progression of Fatty Streaks to Fibrous Plaques in Transgenic Rabbits

Abstract: Whether fatty streaks are directly followed by fibrous plaque formation in atherosclerosis remains controversial. Disruption of the basement membrane and elastic layers is thought to be essential for this process. Matrix metalloproteinase 12 (MMP-12) can degrade a broad spectrum of substrates, but the role of MMP-12 in the early stage of atherosclerosis is unclear. To investigate MMP-12 function in the initiation and progression of atherosclerosis, we investigated macrophage migration and elastolysis in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 38 publications
6
109
1
1
Order By: Relevance
“…mmP-12, a macrophage elastase, was constitutively expressed during development. yamada et al have showed that mmP-12 transgenic rabbits accelerated the initiation of atherosclerosis and stimulated the progression of fatty streaks to fibrous plaques (19). johnson et al have reported that brachiocephalic artery plaques were significantly larger in ApoE/MMP-3 and ApoE/MMP-9 double knockouts compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…mmP-12, a macrophage elastase, was constitutively expressed during development. yamada et al have showed that mmP-12 transgenic rabbits accelerated the initiation of atherosclerosis and stimulated the progression of fatty streaks to fibrous plaques (19). johnson et al have reported that brachiocephalic artery plaques were significantly larger in ApoE/MMP-3 and ApoE/MMP-9 double knockouts compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Since MMP-12 is not only involved in lung tissue remodeling-associated diseases [35,37,41,46,50,[81][82][83][84][85][86][87][88][89], substantial efforts have been made to develop MMP-12 synthetic inhibitors. However, inhibiting a specific MMP is a difficult goal because of the high conservation between many MMPs in terms of overall 3D-structure, topology of the catalytic domain and requirement of specific amino-acid residues in the active site [90,91].…”
Section: Most Efficient Mmp-12 Chemical Inhibitorsmentioning
confidence: 99%
“…Recently, Yamada and coworkers have investigated macrophage migration and elastolysis in relation to fatty streaks in human MMP-12 transgenic (hMMP-12 Tg) rabbits, finding that MMP-12 production by macrophages plays a role in the transition from fatty acids to fibrous plaques during the progression of atherosclerosis (Yamada et al, 2008). On the basis of these results a specific MMP-12 inhibitor might eventually turn out to be useful for the treatment of progressive atherosclerosis.…”
Section: Mt6-mmp (Mmp-25)mentioning
confidence: 99%